Invasion biology, ecology, and management of Frankliniella occidentalis in China. Issue 3 (23rd September 2019) - Zhang, Bin; Qian, Wanqiang; Qiao, Xi; Xi, Yu; Wan, Fanghao
Abstract: Frankliniella occidentalis is an economically important invasive pest worldwide, which can damage various horticultural crops and ornamental plants. F. occidentalis was first intercepted in Kunming, Yunnan province in 2000, and first reported to establish a population in Beijing, China in 2003. Since then, this pest is currently distributed across tens of provinces in mainland China and cause increasingly serious damage and loss. To control this pest, invasion biology, monitoring, and integrated pest management have been generally and intensively studied for 15 years in China. Furthermore, western flower thrips (WFT) as an important invasive insect pest, the research achievements on WFT has contributed to the promotion of technological innovation and development for invasive alien species management strategies and techniques in China. This review provides an overview for research on the biology, ecology, prevention, and management of this pest during 15 years in China. Meanwhile, China's "4E action" strategy on F. occidentalis is also discussed in this review. Abstract : The distribution map of Frankliniella occidentalis in mainland China, based on reported provinces.